The real-time monitoring system of blood flow velocity using Doppler ultrasound for healthcare application - Zulaika, Hamdon; Akutagawa, Masatake; Emoto, Takahiro; Kinouchi, Yohsuke; Rasyada, A Rahman; Noor Azmi, Azran Azhim (J- Stage, 2015)
Doppler ultrasound is a widely used and reliable noninvasive device for blood flow waveform measurement. However, the commercialized blood flow devices are usually in hospital with limited access for public, required monitoring by competent staff and not easily transported. The aim of current study is to examine the potential of a portable blood flow velocity (BFV) Doppler ultrasound system for healthcare application. The effects of visceral fat (VF) level, blood pressure (BP) level (hypertension), aging, regular exercise and exercise-trained programme toward blood flow waveforms and its indices are determined. The peak systolic (S1) velocity and resistive index (RI) are significantly higher (p<0.05) in older population who exercise regularly than who does not. There are significant differences (p<0.05) in the RI and velocity reflection index between normotensive and hypertensive groups. The S1 and peak diastolic (D) are decreased significantly (p<0.05) from normotensive to hypertension groups. Low VF group has significantly increase vascular elasticity than high VF group. In contrast, low VF group has decrese reflected wave velocity. Our findings have broad implication in prevention and monitoring of cardio-related healthproblem that possibly early detection by frequent measurement of BFV, BP and electrocardiogram using this portable device.